Exercise in a hot environment: the skin circulation - Johnson, J. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The combined metabolic and thermoregulatory demands of exercise in the heat place an exceptional burden on the circulation, more than can be met through cardiac output and blood flow redistribution. Blood flow to muscle is not reduced by heat stress in exercise and cardiac output is insufficient to meet competing demands from skin and muscle. Skin blood flow during exercise in the heat is limited in several ways. Dynamic exercise causes a cutaneous vasoconstriction at exercise onset through increased vasoconstrictor activity, both in cool and warm conditions. As exercise continues, internal temperature reaches a threshold for increased active vasodilator activity that is elevated by exercise, but reduced by high skin temperature. Beyond that threshold, skin blood flow is limited well below what would be achieved at rest with the same thermal drive through a limit to the active vasodilator system. This combination of restraints on cutaneous vasodilator function compromises temperature regulation. Internal temperature rises to levels that limit exercise through central thermal effects, rather than loss of blood pressure or a reduction in blood flow to active muscle.